Analysis of the Current Situation of Physical Fitness Development of Teenagers and Children in China under the Multimedia Environment - Yu , Yanping (Journal of Theory and Practice of Contemporary Education, 2023)
In the current education system in China, the physical indicators such as endurance and endurance of adolescents and children are gradually decreasing, mainly due to insufficient attention to the development of physical fitness for adolescents, unscientific methods of physical fitness education, and other factors, which restrict the good development of adolescents and children. This article elaborates on the connotation of physical fitness for adolescents and children, analyzes the current situation of physical fitness development for adolescents and children in China, and points out optimization strategies for the physical fitness development of adolescents and children in China under the multimedia environment, including increasing the promotion of the concept of physical fitness, establishing a sound interactive supervision mechanism, developing targeted intervention methods, and emphasizing the cultivation of physical fitness education talents.